Structural characterization of wheat starch granules differing in amylose content and functional characteristics - Blazek, J.; Salman, H.; Lopez Rubio, A.; Gilbert, E.; Hanley, T.; Copeland, L.
Small-angle X-ray scattering (SAXS)together with several complementary techniques, such was differential scanning calorimetry and X-ray diffraction, have been employed to investigate the structural features that give diverse functional properties to wheat starches (Triticum aestivum L.)within a narrow range of enriched amylose content (36-43
Keywords: WHEAT STARCH; TRITICUM AESTIVUM; AMYLOSE; AMYLOPECTIN; SMALL-ANGLE X-RAY SCATTERING; GRANULE STRUCTURE; X-RAY DIFFRACTION; DIFFERENTIAL; CANNING CALORIMETRY